Gadai Emas Prespektif Kepatuhan Syariah dan Hukum di Indonesia - Musa, Musa (Sharia Faculty Islamic Economic Law Study Department, 2020)
In the practice of gold pawning in Islamic banking there are several costs that must be burden by customers. These costs include ujrah, administration, stamp duty, and insurance. Gold pawning transactions in Islamic banking must be identified whether they are in accordance with the concept that was stated or not. On the other hand, the practice of gold pawning is different from the policies issued by DSN. This study aims to determine the review of Islamic compliance and Islamic law against gold pawning in Islamic banking. The research method used is to use literature review, which is taken from books, articles, internet, and opinions of experts in their fields. Viewed from the aspect of sharia compliance, the reality of sharia banks uses as in the theory of sharia compliance policies in the gold mortgage financing process, namely the process of selling collateral and excess sales. While viewed from the aspect of Islamic law, the merging of the rahn and ijarah contracts is related to ta'alluq where the rahn contract is interdependent with the ijarah contract. The matter is permitted by DSN-MUI because between the rahn contract and the ijarah contract have different objects. While seen from the hadith gold pawn contract there are two contracts in one transaction, namely rahn contract and ijarah contract. This matter is prohibited in Islamic teachings.